Search for heavy neutral and charged leptons in e+e- annihilation at √s = 183 and 189 GeV - Dova, María Teresa (1999)
A search for unstable neutral and charged heavy leptons as well as for stable charged heavy leptons is performed at center-of-mass energies √ s = 183 and 189 GeV with the L3 detector at LEP. No evidence for their existence is found. We exclude neutral heavy leptons which couple to the electron, muon or tau family, of the Dirac type for masses below 92.4, 93.3 and 83.3 GeV, and of the Majorana type for masses below 81.8, 84.1 and 73.5 GeV, respectively. We exclude unstable charged heavy leptons for masses below 93.9 GeV for a wide range of the associated neutral heavy lepton mass. If the unstable charged heavy lepton decays to a light neutrino, we exclude masses below 92.4 GeV. The production of stable charged heavy leptons with mass less than 93.5 GeV is also excluded.